Nematode populations affect grapevine seedlings: Understanding the host-parasite interaction is critical for preventing negative effects - Ndifon, E.M. (Ediciones INTA, 2024)
The initial population density of nematodes is a primary factor that determines the damage caused to a crop. However, this factor has not been investigated adequately on grapevine. An investigation of the effects of initial population densities of Meloidogyne incognita on grapevine (cuttings) was carried out using a completely randomized design. The parameters recorded included shoot height, number of leaves, number of tendrils, and nematode population density. Low initial population densities of M. incognita had a stimulatory effect on grapevine growth. However, above 520 nematode eggs per pot, the performance of the crop (i.e. plant height, number of leaves, number of tendrils) started to decline gradually, culminating in the lowest performance at 4160 nematode eggs/pot. The mean nematode population density at the termination of the experiment revealed that the initial population density of 520 nematode eggs/pot resulted in more population build-up (4.73 and 9.55 times more nematodes than in the initial populations in Experiments 1 and 2, respectively) than that of 4160 nematode eggs/pot (with 1.46 and 1.68 times more nematodes than in the initial populations). The tolerance limit of grapevine to M. incognita (circa 520 nematode eggs) infection was determined to be the point where the magnitude of the plant character(s) started to decrease. It was concluded that this nematode is capable of severely disrupting the grapevine sector in tropical regions.